2001
DOI: 10.1128/jcm.39.3.1184-1186.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Mycoplasma pneumoniae in Adults with Community-Acquired Pneumonia Requiring Hospitalization

Abstract: Mycoplasma pneumoniae infection was diagnosed in 18 (12.5%) of 144 adults hospitalized with communityacquired pneumonia. The infection was demonstrated by PCR in 15 patients and by serology, using two methods, in 10 patients. The mean age of the 8 patients with positive M. pneumoniae PCR and negative serology was significantly higher than that of the 10 patients with positive serology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
2
15

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 15 publications
2
39
2
15
Order By: Relevance
“…Räty et al (79) collected sputum, an NPA and a OPS specimen from 32 young military conscripts with pneumonia during an M. pneumoniae outbreak and applied PCR and also concluded that sputum was the best sample to detect M. pneumoniae. Dorigo-Zetsma et al also found that sputum was the specimen that was most likely to be PCR positive (62.5%, versus 41% for nasopharynx, 28% for OPSs, and 44% for throat washes (31). The superiority of sputum in these studies was in agreement with earlier studies when M. pneumoniae was detected by probe hybridization from sputum and OPSs (57) and by antigen detection from sputum and NPAs (56).…”
Section: Gnarpe Et Al (43) Compared Npss Andsupporting
confidence: 82%
“…Räty et al (79) collected sputum, an NPA and a OPS specimen from 32 young military conscripts with pneumonia during an M. pneumoniae outbreak and applied PCR and also concluded that sputum was the best sample to detect M. pneumoniae. Dorigo-Zetsma et al also found that sputum was the specimen that was most likely to be PCR positive (62.5%, versus 41% for nasopharynx, 28% for OPSs, and 44% for throat washes (31). The superiority of sputum in these studies was in agreement with earlier studies when M. pneumoniae was detected by probe hybridization from sputum and OPSs (57) and by antigen detection from sputum and NPAs (56).…”
Section: Gnarpe Et Al (43) Compared Npss Andsupporting
confidence: 82%
“…As presented in this study, definite diagnosis remains dependent on serological tests, which may require several weeks, and the culture of mycoplasma is not practical. Although current rapid diagnostic tools using PCR, which has high specificity and sensitivity, are available [14,15], they may not be applicable in every medical institute. Thus, the development of newer diagnostic tools is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…applied to bronchoalveolar lavage (BAL) fluid has been found useful [8], PCR for Mycoplasma pneumoniae and Chlamydophila pneumoniae has not been evaluated in BAL samples. However, as sputum samples have been shown to be more useful than upper respiratory tract samples for PCR identification of M. pneumoniae [9,10] and C. pneumoniae [11], and because sputum samples can often not be collected in patients with LRTI, BAL PCR could probably be useful for identification of these two pathogens in LRTI patients.…”
mentioning
confidence: 99%